BIODIVERSITAS EKHINODERMATA DI PERAIRAN PANTAI TAKOFI, PULAU MOTI – MALUKU UTARA - Yusron, Eddy (UI Scholars Hub, 2006)
Echinoderm Biodiversity in the Takofi Coastal Waters, Moti Island, North Maluku. A total of 22 echinoderm species were found in Takofi waters, North Maluku. They were represented by 6 species of holothuroidea, 4 species of asteroidea, 5 species of echinoidea and 7 species of ophiuroidea. The Ophiuroidea were relatively common in seagrass area. The quantitative analysis on the abundance data revealed the highest diversity index of faunal assemblage at station II (H’=1.19). The highest evenness index was exhibited by the echinoderms from station III (J = 0.99), while the highest species richness was represented by them from station I (D = 1.22).